2018
DOI: 10.1186/s12913-018-3252-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ ability to read and understand dosing instructions of their own medicines – a cross sectional study in a hospital and community pharmacy setting

Abstract: BackgroundPoor communication of medicines information to patients may cause medication errors. We assessed the completeness and readability of dosing instructions provided by pharmacists on dispensing labels and knowledge among patients on dosing instructions of their medicines.MethodsA cross sectional study was conducted in a selected teaching hospital, and a community pharmacy, among 800 patients selected through a systematic sampling method, during a period of 2 months. Completeness of dosing instructions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…In another study conducted by us in the same study settings, it was found that dosing instructions were not 100% complete, and patients were not able to completely read or understand dosing instructions provided. (7) This finding too reconfirms the serious gap in the communication process as highlighted by pharmacists. (7) When considering verbal instructions, linguistically accessible medication instructions are particularly important to ensure patient safety.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In another study conducted by us in the same study settings, it was found that dosing instructions were not 100% complete, and patients were not able to completely read or understand dosing instructions provided. (7) This finding too reconfirms the serious gap in the communication process as highlighted by pharmacists. (7) When considering verbal instructions, linguistically accessible medication instructions are particularly important to ensure patient safety.…”
Section: Discussionmentioning
confidence: 85%
“…(7) This finding too reconfirms the serious gap in the communication process as highlighted by pharmacists. (7) When considering verbal instructions, linguistically accessible medication instructions are particularly important to ensure patient safety. In an American study, it was found that more than 80% of the pharmacies surveyed, lacked systematic methods for identifying linguistic needs of patients and the need for translation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Medication knowledge was assessed for each medication taken using an assessment of drug dose (D), frequency (F), indication (I), and administration (T) (DFIT) [19,20]. Medications knowledge was measured based on the number of correct responses as a correct answer was scored as '1', whilst an incorrect answer was scored '0' [19,20]. The total score for each medication was calculated based on the number of correct answers; [number of correct answers/4] x100% [19,20].…”
Section: Data Collectionmentioning
confidence: 99%
“…Medications knowledge was measured based on the number of correct responses as a correct answer was scored as '1', whilst an incorrect answer was scored '0' [19,20]. The total score for each medication was calculated based on the number of correct answers; [number of correct answers/4] x100% [19,20]. An overall knowledge score was determined by determining the average score of all medications.…”
Section: Data Collectionmentioning
confidence: 99%